2020
DOI: 10.1038/s41561-020-00655-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent recovery of Antarctic Bottom Water formation in the Ross Sea driven by climate anomalies

Abstract: Antarctic Bottom Water (AABW) supplies the lower limb of the global overturning circulation, ventilates the abyssal ocean and sequesters heat and carbon on multidecadal to millennial timescales. AABW originates on the Antarctic continental shelf, where strong winter cooling and brine released during sea ice formation produce Dense Shelf Water, which sinks to the deep ocean. The salinity, density and volume of AABW have decreased over the last 50 years, with the most marked changes observed in the Ross Sea. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 62 publications
6
98
1
Order By: Relevance
“…The easternmost float, located in the southeast corner of the basin at ~150°E, captured the youngest RSBW in the basin that flows in from the east around Cape Adare (Figure 1; float 12008, red). Consistent with Silvano et al, 2020, the February 2018 occupation of the 150°E line showed that the deep waters here had warmed by 0.1°C and increased in salinity by 0.03 since the last occupation in 2011. The float data in 2019 also show the densest water between 46.16 and 46.18 kg/m 3 σ 4 have increased salinity by 0.04 compared to the 2011 hydrographic data, a rebound not seen in waters of similar density at the western end of the basin (Figure 2c; float 12008, red).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The easternmost float, located in the southeast corner of the basin at ~150°E, captured the youngest RSBW in the basin that flows in from the east around Cape Adare (Figure 1; float 12008, red). Consistent with Silvano et al, 2020, the February 2018 occupation of the 150°E line showed that the deep waters here had warmed by 0.1°C and increased in salinity by 0.03 since the last occupation in 2011. The float data in 2019 also show the densest water between 46.16 and 46.18 kg/m 3 σ 4 have increased salinity by 0.04 compared to the 2011 hydrographic data, a rebound not seen in waters of similar density at the western end of the basin (Figure 2c; float 12008, red).…”
Section: Resultssupporting
confidence: 91%
“…Decadal occupations of hydrographic sections gridding the deep ocean conducted by the Global Ocean Ship‐based Hydrographic Investigations Program (GO‐SHIP; Talley et al, 2016) have shown that the abyssal ocean has warmed significantly throughout the globe (Desbruyères et al, 2016; Fukasawa et al, 2004; Kawano et al, 2006; Kouketsu et al, 2011; Purkey & Johnson, 2010). This deep warming is likely driven by changes in the salinity of the dense shelf waters around Antarctica that produce AABW (e.g., Aoki et al, 2005, 2013; Kobayashi, 2018; Menezes et al, 2017; Purkey & Johnson, 2012, 2013; Rintoul, 2007; Shimada et al, 2012; van Wijk & Rintoul, 2014), which have undergone short‐ and long‐term variability owing to increased glacial runoff and interannual variability in sea ice production and export (Castagno et al, 2019; Jacobs et al, 2002; Jacobs & Giulivi, 2010; Silvano et al, 2020). Furthermore, high resolution models have shown a similar climate signal of abyssal warming, driven by a combination of decreased AABW production from anthropogenic freshening and warming on the shelves near Antarctica and from warmer waters being advected through the bottom limb of the MOC (Boé et al, 2009; Bryan et al, 2014; Newsom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CALM observations show a slight decrease of salinity of 0.007/year 11 , also consistent with the observations in the Ross Sea. The recent salinity increase has been linked to increase in sea ice production in the Ross Sea 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The connections between the interannual variability of the wind stress and large‐scale indices and of regional parameters have been extensively investigated in the literature, defining how the interaction between SAM index and ENSO can influence the general SO circulation (Cerrone, Fusco, Cotroneo, et al, 2017), its sea ice cover (Cerrone, Fusco, Simmonds, et al, 2017; Cerrone & Fusco, 2018), its mixed layer depth (Buongiorno Nardelli et al, 2017), and even the surface heat fluxes at regional scales (Fusco et al, 2018). Recently, Silvano et al (2020) demonstrated how the combined effect of the ENSO and the SAM state can affect the sea ice formation in the Ross Sea, explaining the recent reversal of the salinity trend observed in the Ross Sea (Castagno et al, 2019). The ability of El Niño to mitigate the effect of the strong SAM is already described by Morrow et al (2010), Fogt et al (2011), and Langlais et al (2015).…”
Section: Discussionmentioning
confidence: 99%